Senam pinggul dan kualitas hidup ibu menopause - Sekunda, Maria Salestina; Bai, Marieta K S; Cahyani, Sisilia Leny (Poltekkes Kemenkes Kupang, 2023)
Introduction: Menopause is very complex for women because they will experience changes in physical health that affect their psychological health. The purpose of the study was to determine the contribution of hip exercise to improving the quality of life of postmenopausal women in Ende district. Methods: The type of research is experimental, observational design. The number of samples was 48 menopausal women who had complaints with total sampling technique. The study was conducted in July and August 2019. Data analysis used the Wilcoxon Signed Rank test. Results: The results showed that there was a change in passion for life through complaints in menopausal women before and after giving hip exercises in Ende district as indicated by the -value for vasomotor, psychological, physical and somatic complaints. Asymp. Sig (2-tailed): 0.000 where value < 0.05. Conclusion: Hip exercise can increase the passion of menopausal women. Therefore, it is hoped that postmenopausal women need to increase their physical activity through gymnastics, especially pelvic floor exercises which can reduce complaints during the menopausal period.